Green Shipping in Major Countries: An Approach towards Shipyards, Shipping Companies, Ports and Policies - Lee, Taehee; Nam, Hyunjeong (New Innovations in Economics, Business and Management Vol. 10, 2022)
The objective of this research is to define green shipping and environmentally friendly vessels, as well as to identify the regulations and current market situation in major countries like Europe, the United States, Japan, China, and South Korea, in terms of shipping companies, shipyards, ports, and policies. Eco-friendly vessels are those that comply with the IMO Conventions, which came into effect in accordance with IMO regulations. Despite the fact that commercialization is still limited, the introduction of environmentally friendly vessels is required to meet the environmental regulations of international ports and ports in developed countries, as well as to handle the replacement of bunker oil, which is fraught with uncertainty and accounts for the majority of the shipping industry's operating costs. Based on prior literature as well as the examples of each stakeholder in key nations, this conceptual study defines and evaluates the current market condition of green shipping. As a result of the findings, this study identifies six significant issues and suggests solutions to improve strategic planning in South Korea in preparation for green shipping. Technological development should be supported for not only shipbuilders and large shipyards, but also suppliers, trading partners, small- and medium-sized shipyards, academics, and researchers in order to develop the related equipment and parts technology.